PENGARUH HUMAN CAPITAL TERHADAP KINERJA BUILDING MANAGEMENT PADA PENGELOLAAN GEDUNG MENARA BOSOWA MAKASSAR - Mashur Razak; Haeruddin Haeruddin (AkMen JURNAL ILMIAH, 2018)
This research aims is to know and to analyze the impact of human capital (individual capability, individual motivation, leadership, the organization climate, and workgroup effectiveness) to performance Building Management of Menara Bosowa Makassar. This research using the survey method with the amount of sample 71 respondent, it is analyzed using program of SPSS 23. This research shows that :1) individual capability have positive and insignificant effect to Menara Bosowa Building Management performance; 2) individual motivation has positive and significant effect to Menara Bosowa Building Management performance; 3) leadership has positive but not significant effect to Menara Bosowa Building Management performance; 4) the organization climate has positive and significant effect to Menara Bosowa Building Management performance 5) workgroup effectiveness gives positive and significant effect to Menara Bosowa Building Management performance.